2019
DOI: 10.1121/1.5091776
|View full text |Cite
|
Sign up to set email alerts
|

Mice can learn phonetic categories

Abstract: Speech is perceived as a series of relatively invariant phonemes despite extreme variability in the acoustic signal. To be perceived as nearly-identical phonemes, speech sounds that vary continuously over a range of acoustic parameters must be perceptually discretized by the auditory system. Such many-to-one mappings of undifferentiated sensory information to a finite number of discrete categories are ubiquitous in perception. Although many mechanistic models of phonetic perception have been proposed, they rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
(76 reference statements)
2
8
0
Order By: Relevance
“…We digitized the signal at 176 kHz and then decimated down to 44.1 kHz. Because much of the frequency content of human speech is below the mouse hearing range (which is approximately 1-80 kHz), we pitch-shifted the speech upward by one octave using a frame-based algorithm with Fourier transforms of window length 2048, analysis length 512, and synthesis length 1024 samples (Saunders and Wehr, 2019). The resulting pitch-shifted stimuli had preserved temporal structure and a sample rate of 88.2 kHz ( Figure 1B).…”
Section: Stimulimentioning
confidence: 99%
“…We digitized the signal at 176 kHz and then decimated down to 44.1 kHz. Because much of the frequency content of human speech is below the mouse hearing range (which is approximately 1-80 kHz), we pitch-shifted the speech upward by one octave using a frame-based algorithm with Fourier transforms of window length 2048, analysis length 512, and synthesis length 1024 samples (Saunders and Wehr, 2019). The resulting pitch-shifted stimuli had preserved temporal structure and a sample rate of 88.2 kHz ( Figure 1B).…”
Section: Stimulimentioning
confidence: 99%
“…Reward Volume (uL) Successful Mice Figure 2.4: "Minor" details have major effects. Proportion of mice (each point, n=4) that were successful learning the first stage of the speech task described in [31] across 10 behavior boxes with variable reward sizes. A 2µL difference in reward size had a surprisingly large effect on success rate.…”
Section: Message Handlingmentioning
confidence: 99%
“…Similarly, the ability to identify versions of learned sounds (vLS) has been studied in songbirds, ferrets, and mice. [3][4][5] Rhesus monkeys and chimpanzees acknowledge vocalizations for foods of different values and from various troop members. 6,7 Although this ability is vital for communication, the neural basis for the invariant recognition of sounds is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…9 A recent study in mice found that they discriminate the consonants (/g/ and /b/) and still recognize them when combined with different vowels or emitted by other speakers. 5 Nevertheless, understanding the neuronal correlates of invariant perception of complex sounds such as words, requires active recognition during neurophysiological recordings.…”
Section: Introductionmentioning
confidence: 99%